MODERN TRENDS IN HR FOR RETENTION STRATEGIES IN IT SECTOR (International Journal of Food and Nutritional Sciences, 2018)
The business world has become one with the advent of the term globalization. This has created a pool of talent which is ready to be grabbed by various organizations during the year 1990, in India after globalization, liberalization and Privatization, India Telecom Sector was under the control of Govt. In 1994 Govt. was announced to privatize the telecom sector. After privatization, company focus their core functions and are interested to outsource the major non core functions, Non core functions like, Call centre services, data entry, HR services, Medical Billing, accounting, customer care, biotech research, IT software etc.